Evaluation of the Implementation of Elderly Posyandu in the Working Area of Petumbukan Health Center, Deli Serdang Regency - Darmanto Ginting (JURNAL KESMAS DAN GIZI (JKG), 2026)
Elderly healthcare services have become a national priority in response to the increasing aging population in Indonesia. Posyandu Lansia (Integrated Health Services for the Elderly) is a community-based health initiative aimed at improving the quality of life of elderly individuals through promotive, preventive, and routine health monitoring activities. This study aims to evaluate the implementation of Posyandu Lansia in the working area of Petumbukan Health Center, Deli Serdang Regency, focusing on elderly participation rates, service availability, the role of health cadres, and existing challenges.This research uses a descriptive method with both qualitative and quantitative approaches. Data collection techniques include field observation, in-depth interviews, and document review. The evaluation findings indicate that while the Posyandu Lansia activities are conducted regularly, the participation rate remains relatively low, at around 35–40%. Available services are limited to basic health checks such as blood pressure and blood glucose monitoring, as well as elderly exercise sessions. Key challenges include limited medical equipment, lack of cadre training, low family involvement, and insufficient operational funding.Improving cadre capacity, ensuring adequate facilities and equipment, and fostering stronger collaboration between the health center, village government, and the community are essential to enhance the sustainability and quality of elderly health services.